Exploring the response of Marchantia polymorpha: Growth, morphology and chlorophyll content in the presence of anthracene - Spinedi, Nahuel (2019)
Polycyclic aromatic hydrocarbons (PAHs) were identified as hazardous contaminants that are ubiquitous and persistent in aquatic environments, where bryophytes sensu lato (mosses, liverworts and hornworts) are frequently present. Marchantia polymorpha (Class Hepaticae; thalloid liverwort) is known to respond fast to changes in the environment; it accumulates toxic substances in its tissues due to the lack of vascular and radicular systems and a reduced or absent cuticle. The objective of the present study was to quantify the effects of increasing concentrations of anthracene (0, 50 100, 280 μM) on the germination of propagules, plant morphology and chlorophyll content index (CCI) in M. polymorpha under in vitro cultures. The results show that anthracene had no statistical effect on germination or propagula formation. However, plants exposed to anthracene for 30 days showed significantly lowered the content of chlorophyll (measured as CCI), irregular growth patterns and the induction of thalli asexual reproduction as evidenced by the production of multicellular viable propagules in gemmae cups. Results of epifluorescence microscopy also showed concomitant accumulation of anthracene in the cell walls. All of these distinctive morphological and physiological adaptive responses indicators, clearly suggest that M. polymorpha are capable of resisting high (coal tar) anthracene concentrations.